Supersized contorted aromatics - Xiao, Shengxiong; Kang, Seok Ju; Wu, Ying; Ahn, Seokhoon; Kim, Jong Bok; Loo, Yueh-Lin; Siegrist, Theo; Steigerwald, Michael L.; Li, Hexing; Nuckolls, Colin (ROYAL SOC CHEMISTRY, 2013)
We describe here the synthesis and electronic device properties of a new type of polycyclic aromatic molecule, the contorted octabenzocircumbiphenyl (c-OBCB). Contorted polycyclic aromatic hydrocarbons (PAHs) are promising small active molecules for organic devices. We present two different methods to synthesize c-OBCB derivatives that allow the smooth incorporation of functional groups. The material has a highly contorted exterior with six 4-helicenes and two 5-helicenes around the exterior of the expanded core of the aromatic. With appropriate sidechains, the material is soluble in common organic solvents and forms thin films. In thin films, the tetradodecyloxy-substituted c-OBCB self-assembles to form the active layer in organic field effect transistors. It is a hole transporting organic semiconductor. In the transistors, the c-OBCB forms good contact with source and drain contacts made from graphene. The c-OBCB self-assembles into a heterojunction from solution with phenyl-C-70-butyric acid methyl ester (PC70BM). We observed power conversion efficiencies of similar to 2.9% under 100 mW cm(-2) illumination at a 1 : 4 weight ratio of the c-OBCB relative to PC70BM. The c-OBCB is shape complementary to the ball shaped PC70BM.
Keywords: OLEFIN SYNTHESIS; HYDROCARBONS; GRAPHENES